Analisis Konsumsi Energi Rumah Tangga Petani Kelapa Sawit di Desa Airapa Kecamatan Sinunukan Kabupaten Mandailing Natal - Sari, Nurvita; Gusriati; Herda Gusvita (Jurnal Research Ilmu Pertanian, 2022)
The purpose of this study was to study the energy consumption of oil palm farmer households and to analyze the factors that influence energy consumption in Airapa Village, Sinunukan District, Mandailing Natal Regency. This research was conducted in June 2021. The location of the study was determined purposively with a total sample of 64 people. The data used are primary data and secondary data. The analytical method used in this research is quantitative descriptive method using multiple linear regression analysis. Using the SPSS version 20 program, the results showed that the energy consumption of oil palm farmers' households in Airapa Village, Sinunukan District, Mandailing Natal Regency averaged 1,896.70 kcal/capita/day or an energy consumption level of 86.21%. Variables that have a significant effect on household energy consumption of oil palm farmers in Airapa Village, Sinunukan District, Mandailing Natal Regency partially are income and food expenditure variables. Meanwhile, simultaneously (simultaneously) are household income variables, food expenditure, number of family members, mother's age, education of the head of the family with (sig 0.000 <0.05). The coefficient of determination (R2) in this study was 82.4%, meaning that the variables of household income, food expenditure, number of family members, mother's age, education of the head of the family contributed 82.4% to energy consumption.